Association between TGF-β1 Polymorphisms and Head and Neck Cancer Risk: A Meta-Analysis - Shi, Quan; Wang, Xing; Cai, Chuan; Yang, Shuo; Huo, Na; Liu, Hongchen (Frontiers in Genetics, 2017)
Background and Objective: Studies have been conducted to explore the association between the single nucleotide polymorphisms (SNPs) in transforming growth factor beta 1 (TGF-β1) and head and neck cancer (HNC) susceptibility, however the findings are still inconclusive. Therefore, we conduct this meta-analysis to quantitatively assess the association. Methods: Embase and PubMed were searched for all eligible clinical studies. The odds ratio (OR) and 95% confidence interval (CI) of each study were pooled to estimate the association between SNPs in the TGF-β1 and the HNC risk. Subgroup analysis was used to explore whether particular characteristics were related to the value of overall ORs and 95% CIs. Results: Seven case-control studies, including three SNPs (−509C/T, 869T/C, and 915G/C), were examined. Overall, this meta-analysis failed to identify a significant association between TGF-β1−509C/T, 915G/C polymorphism and HNC risk in any models. As for the 869T/C polymorphism, significant associations were observed in the allelic model (C vs. T: OR = 1.351, 95%CI: 1.030–1.772), the homozygote model (CC vs. TT: OR = 1.585, 95%CI: 1.026–2.449) and the dominant model (CT/CC vs. TT: OR = 1.398, 95%CI: 1.008–1.937). This polymorphism was also found in the Asian group as well (C vs. T: OR = 1.400, 95%CI: 1.003–1.956, CC vs. TT: OR = 1.814, 95%CI: 1.018–3.233). Conclusion: Meta-analysis failed to show a statistical association between TGF-β1−509C/T, 915G/C polymorphism, and HNC risk in any genetic models. However, it was found that TGF-β1 869C/T polymorphism may be involved in susceptibility to HNC, especially in Asian patients. However, given the limitations of this meta-analysis, further well-designed studies are required in the future.